Aggeavating factors of Burnout Syndrome in Nursing professionals (Research, Society and Development, 2021)
The Professional Burnout Syndrome or Burnout Syndrome (BS), in turn, is related to stress at work at levels that exceed the possibility of adaptation. Thus, occupational stress is a public health problem characterized by a multifactorial cause of injury, arising from the relationship between workers and their environment. This is an integrative literature review. The following steps are followed: identification of the topic and selection of the research, elaboration of inclusion and exclusion criteria, selection of studies, categorization of selected studies, analysis and interpretation of results. After applying the inclusion and exclusion criteria, the corpus of analysis consisted of 14 articles. It was found that the organization of work exerted a strong influence on the psychological impairment of nursing professionals, which may occur after negative experiences, the gradual wear of the subject resulting in a symptomatological picture such as the presence of anxiety, depression, headache, agitation and irritability. Thus, it is worth noting that the symptoms appear differently in each worker. The emotional state of professionals working in closed sectors changes during the shift as it may be associated with the wear and stress of the activity of providing the patient with assistance and care, mainly due to the existence of high levels of skill and knowledge that require a response immediate. The findings of this article show the need to monitor the working conditions and health of these professionals, furthermore, it is necessary to implement strategies that can minimize damage to their health.